Analisis Nilai Toleransi dalam Konten ‘’Login’’ Habib Ja’far di Youtube Deddy Corbuzier - Sinta Amanda (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2024)
This study examines the values of interfaith tolerance in the digital da’wah of Habib Husein Ja'far Al-Hadar through the "Login" content on Deddy Corbuzier's YouTube channel. Utilizing a qualitative method with a phenomenological approach, this research analyzes five videos featuring dialogues between Habib Ja'far and religious figures from Buddhism, Christianity, Hinduism, Confucianism, and Islam. The analysis reveals that Habib Ja'far effectively conveys messages of tolerance by emphasizing values such as mutual respect, understanding, and acceptance of diversity. These values are presented with a humorous style that lightens the atmosphere. Habib Ja'far not only fosters an inclusive interfaith dialogue but also encourages viewers to practice tolerance in their daily lives. This study underscores the significance of social media as a platform for da’wah in promoting interfaith understanding within an increasingly pluralistic society.